FACEBOOK AND RURAL COMMUNITIES: AN ANALYSIS OF SOCIAL COMPARISON AND OVERSHARING THROUGH ERVING GOFFMAN DRAMATURGICAL PERSPECTIVE - Muh Ali Bagas (Jurnal EMPATI, 2025)
This study essentially focuses on analyzing social comparison and oversharing among rural Facebook users. The type of research used is descriptive qualitative field research with a visual ethnography approach. Data analysis used an interactive data analysis model and was analyzed through Erving Goffman's dramaturgical perspective. The results of the study indicate that social comparison and oversharing are manifestations of rural Facebook users' efforts to control their self-image on the front stage. Social comparison focuses on maintaining status through comparison, while oversharing focuses on building authenticity through backstage disclosure. However, these two behaviors can often lead to conflict. The data shows that the majority of posts (76.4%) of Facebook users are at moderate-to-severe risk. Or in other words, this data reflects a lack of awareness of the boundaries between public performance and private life. In addition, this study provides recommendations on existing implications, namely: a) rural communities need to understand and apply digital literacy to understand privacy risks; b) rural communities need to understand and use social media privacy features; c) rural communities need to distinguish between information that is appropriate to share and sensitive information. In short, this study shows that the social behavior of rural communities on Facebook social media is a complex performance that requires a balance between public impressions and personal privacy.